PROSES PENYIDIKKAN TERHADAP PELAKU TINDAK PIDANA PUNGUTAN LIAR SECARA TERORGANISIR (STUDI DI KEPOLISIAN SAT RESKRIM POLRES BINJAI) - Sutardjo, Romadhoni; Sahari, Alpi (JURNAL DOKTRIN REVIEW, 2023)
The behavior of illegal levies in the jurisdiction of the Binjai Police is still found to be carried out by civil servants and some are carried out by groups of people who engage in thuggery around public facilities such as bus terminals, train stations and so on. Because extortion has become very widespread in public services, the Government issued Presidential Decree no. 87 of 2016 concerning the Task Force to Clean Up Illegal Levies, this Presidential Decree was issued because the practice of illegal levies has damaged the life of society, the nation and the state so that efforts to eradicate it are needed in a firm, integrated, effective, efficient and capable of having a deterrent effect. This research discusses criminal law provisions for perpetrators of criminal acts of illegal levies, and law enforcement efforts by the Binjai Police Criminal Investigation Unit against perpetrators of criminal acts of illegal levies, as well as obstacles found by the Binjai Police Criminal Investigation Unit in carrying out law enforcement against perpetrators of criminal acts of illegal levies. This research method is empirical juridical legal research. The legal provisions for illegal levies can be identified with extortion, threats, fraud, even gratification, corruption. Efforts to enforce the law against perpetrators, by maintaining security and public order, are based on the nature of the Police's duties with Pre-emptive, Preventive and Repressive functions. The obstacles found were overlapping legal regulations, limited police personnel, lack of facilities and facilities, weak organizational resource capacity of the Binjai Police. It would be better for the crime of illegal levies to have its own legal provisions in the Criminal Code, so that it no longer uses the Articles of Extortion or fraud, and it would be better for law enforcement not only to be given less prison sanctions but to be given fines and restitution.